The Enrichment of Calcium with Duck Eggshell and Sensory Characteristic on Product Based on Corn Sprout Flour and Soybean Sprout Flour - Siti Aminah; Wulandari Meikawati (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2017)
Eggshell duck is one of the ingredients that can be used for supplementation enriching calcium in food products. Corn flour and soybean (kejale) formulation have contribute to health. Enrichment of calcium with eggshell duck will be improve the quality kejale. This study aims to evaluate the levels of calcium and the sensory characteristics of cookies products, steamed cakes and kejale based cereals, enriched with eggshell duck as a source of calcium. The results showed that the enrichment treatment of eggshell duck influenced the calcium cookies, steamed cakes and cereals (p = 0,00). Levels of calcium cookies and steamed cakes are higher than cereals. The sensory characteristics showed that the enrichment of eggshell duck doesn’t affect the taste, smell and texture but affect the color. Being on eggshell duck affects the color, smell and texture, but no effect ontaste. Eggshell duck concentration at 15% concentration provides the highest levels of calcium and acceptablesensory characteristics. Keywords: Calcium, eggshell duck, sensory, corn flour, soybean flour